Cardiomyocyte BRAF and type 1 RAF inhibitors promote cardiomyocyte and cardiac hypertrophy in mice in vivo. Issue 3 (11th February 2022) - Clerk, Angela; Meijles, Daniel N.; Hardyman, Michelle A.; Fuller, Stephen J.; Chothani, Sonia P.; Cull, Joshua J.; Cooper, Susanna T.E.; Alharbi, Hajed O.; Vanezis, Konstantinos; Felkin, Leanne E.; Markou, Thomais; Leonard, Samuel J.; et al.
Abstract : The extracellular signal-regulated kinase 1/2 (ERK1/2) cascade promotes cardiomyocyte hypertrophy and is cardioprotective, with the three RAF kinases forming a node for signal integration. Our aims were to determine if BRAF is relevant for human heart failure, whether BRAF promotes cardiomyocyte hypertrophy, and if Type 1 RAF inhibitors developed for cancer (that paradoxically activate ERK1/2 at low concentrations: the 'RAF paradox') may have the same effect. BRAF was up-regulated in heart samples from patients with heart failure compared with normal controls. We assessed the effects of activated BRAF in the heart using mice with tamoxifen-activated Cre for cardiomyocyte-specific knock-in of the activating V600E mutation into the endogenous gene. We used echocardiography to measure cardiac dimensions/function. Cardiomyocyte BRAF V600E induced cardiac hypertrophy within 10 d, resulting in increased ejection fraction and fractional shortening over 6 weeks. This was associated with increased cardiomyocyte size without significant fibrosis, consistent with compensated hypertrophy. The experimental Type 1 RAF inhibitor, SB590885, and/or encorafenib (a RAF inhibitor used clinically) increased ERK1/2 phosphorylation in cardiomyocytes, and promoted hypertrophy, consistent with a 'RAF paradox' effect. Both promoted cardiac hypertrophy in mouse hearts in vivo, with increased cardiomyocyte size and no overt fibrosis. In conclusion, BRAF potentially plays an important role in human failing hearts, activation of BRAF is sufficient to induce hypertrophy, and Type 1 RAF inhibitors promote hypertrophy via the 'RAF paradox'. Cardiac hypertrophy resulting from these interventions was not associated with pathological features, suggesting that Type 1 RAF inhibitors may be useful to boost cardiomyocyte function.